Conservative management of penile fracture: a case report - Ahlan Syaheza; Rudi Haris Munandar; Dahril (Journal of International Surgery and Clinical Medicine, 2022)
Background: One of the uncommon emergencies in urology is a penile fracture. Due to blunt trauma to the erect penis, the tunica albuginea of one or both corpus cavernosum was disrupted, a rare kind of urologic damage. Corpus spongiosum or urethral rupture and dorsal nerve and vascular injury may also be present. Here, we describe a penile fracture case that was successfully treated conservatively at Zainoel Abidin Hospital. Case report: A 38-year-old male who had been having sex an hour before and had meatal bleeding, a history of cracking noises, and rapid detumescence presented to the emergency room at Zainoel Abidin Hospital. The patient also had pain when urinating. Physical examination revealed an enlarged penis and meatal hemorrhage but no ecchymosis or eggplant-like appearance. No bladder is full. The Foley catheter was put in. on ultrasonography of the penile. The hematoma was present in the corpus cavernous and spongiosum, and the urethra lumen was uneven. A pendulous urethral rip about 5 mm in size was found during urethroscopy. After 2 days of observation, the erectile function returned without pain or menstrual blood. After two days of conservative therapy, the patient was discharged from the hospital. Conclusion: Conservative treatment of the penile fracture is still an option based on clinical findings in cases.